Cascade Fumarate Hydratase mutation screening allows early detection of kidney tumour: a case report - Melanie M. Y. Chan; Angela Barnicoat; Faiz Mumtaz; Michael Aitchison; Lucy Side; Helen Brittain; Alan W. H. Bates; Daniel P. Gale (BMC, 2017)
Abstract Background Fumarate hydratase (FH) deficiency is a rare autosomal recessive disorder which results in a major defect in cellular metabolism. It presents in infancy with progressive encephalopathy, hypotonia, seizures and failure to thrive and is often fatal in childhood. It is caused by mutations in the FH gene (1q42.1) that result in deficiency of the citric acid cycle enzyme fumarate hydratase, resulting in accumulation of fumaric acid. Heterozygous germline mutations in the FH gene predispose to an aggressive autosomal dominant inherited early-onset kidney cancer syndrome: hereditary leiomyomatosis and renal cell cancer (HLRCC). Case presentation Cascade FH mutation screening enabled the early diagnosis of a renal tumour in an asymptomatic parent of a child with fumarate hydratase deficiency, resulting in timely and possibly life-saving treatment. Conclusion While the theoretical risk of kidney cancer in parents of children with recessive fumarate hydratase deficiency is well recognized, to our knowledge this is the first report of a kidney tumour being detected in a parent by screening performed for this indication. This underscores the importance of offering lifelong kidney surveillance to such parents and other heterozygous relatives of children born with fumarate hydratase deficiency.